2013
DOI: 10.5101/nbe.v5i1.p10-19
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Bio-Molecules Assisted – Rod / Spherical shaped Lead Nano Powder Synthesized by Electrolytic Process and Its Characterization Studies

Abstract: Synthesis and structural characterization of Pb nanoparticles by electrolysis using a bioactive compound -konjac aqueous extract is the main aim of this study. This method is a unique, novel, low cost and double-step procedure with good reproducibility and has not been used for nanoparticles preparation so far. Konjac extract has been added to prevent the oxidation of Pb nanoparticles. Also the synthesized nanoparticles have been dried in open air to observe their stability. Various types of characterization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…These changes differed from one treatment to another according to the type of used dietary fiber and it's addition ratio. Treatments made by adding konjac fiber gained the highest protein content either at zero time or during the storage period, when compared with the with the maltodextrin , These results agree with Theivasanthi and Alagar, (2012), who reported that Konjac fiber is highly nutritious , with over 45%of glucommans ,9.7% of crude protein , 16 different kinds of amino acid .…”
Section: Ts Ph Valuessupporting
confidence: 89%
See 1 more Smart Citation
“…These changes differed from one treatment to another according to the type of used dietary fiber and it's addition ratio. Treatments made by adding konjac fiber gained the highest protein content either at zero time or during the storage period, when compared with the with the maltodextrin , These results agree with Theivasanthi and Alagar, (2012), who reported that Konjac fiber is highly nutritious , with over 45%of glucommans ,9.7% of crude protein , 16 different kinds of amino acid .…”
Section: Ts Ph Valuessupporting
confidence: 89%
“…It is highly nutritious, with over 45% of glucomannan, 9.7% of crude protein, 16 different kinds of amino acids up to 7.8%, 7 essential amino acids up to 2.5% , low fat and high in fiber. Glucose fructose and sucrose are also present in konjac (Theivasanthi and Alagar, 2012). So, this work aims to study the effects of dietary fiber incorporation on the quality of plain yoghurt fermented with traditional yoghurt starter.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the sharper the graphite peak appears on a material XRD spectrum, the higher the crystallinity is [24]. However, the shape of the graphite peak is dependent on the copper element intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it has glucose, fructose and sucrose presents in konjac. Moreover, it have over 45% glucomannan, different types of amino acids contain 7 essential amino acids, 9.7% of crud protein, low fat and high in fiber Theivasanthi and Alagar ( 2012).…”
Section: Introductionmentioning
confidence: 99%